Teachers' Directive Speech Acts in The Teaching and Learning Process of The Independent Campus Program - Narulita, Fanesa; Arifin, Zainal (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Directive speech acts are expressions used by speakers directed towards interlocutors to create an expression of the speaker’s intentions or desires. This serves as one of the reasons for the interlocutor to take specific action. The author has chosen to focus on directive speech acts in the teaching and learning process within the independent campus program. The objective of the research is to identify directive speech acts employed by teachers during the teaching and learning process. The data source for this research consists of teachers’ utterances during the teaching and learning process at SD Negeri 2 Sukorejo, located in Pacalan Village, Sukorejo, Kecamatan Wedi, Kabupaten Klaten. This research falls under the qualitative category because it aims to generate data in the form of words, expressions, speech, or sentences related to teachers’ directive speech acts in online learning at SD Negeri 2 Sukorejo. Data collection for this research utilizes the Simak Bebas Libat Cakap (SBLC) technique, recording technique, and note-taking technique. The analysis of research data employs the pragmatic equivalent method. The findings of this research reveal various forms of teacher directive speech acts during the teaching and learning process, including requests (25%), plead (7%), invite (17%), push (11%), asking (16%), commanding (11%), prohibiting (5%), permitting (4%), reminding (4%).